Genome sequence and description of Alterileibacterium massiliense gen. nov., sp. nov., a new bacterium isolated from human ileum of a patient with Crohn's disease. (July 2019) - Boxberger, M.; Anani, H.; La Scola, B.
Abstract: Alterileibacterium massiliense gen. nov. sp. nov. strain Marseille-P3115 T (= CSURP-3115; DSM 103486), formerly proposed as Ileibacterium massiliense, is a new genus of bacteria isolated from the ileum of a human patient with Crohn's disease.